2012
DOI: 10.1016/j.stem.2012.05.027
|View full text |Cite
|
Sign up to set email alerts
|

FLT3-ITD Knockin Impairs Hematopoietic Stem Cell Quiescence/Homeostasis, Leading to Myeloproliferative Neoplasm

Abstract: SUMMARY Internal tandem duplication (ITD) mutations within the FMS-Like Tyrosine Kinase gene (FLT3) render the receptor constitutively active, driving proliferation and survival in leukemic blasts. Expression of Flt3-ITD from the endogenous promoter in a murine knock-in model results in progenitor expansion and a myeloproliferative neoplasm. In this study, we show that this expansion begins with over-proliferation within a compartment of normally quiescent long-term hematopoietic stem cells (LT-HSCs), which be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
85
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 68 publications
12
85
1
Order By: Relevance
“…7 C). A similar phenotype has been described previously in an Flt3-ITD animal model (Chu et al, 2012).…”
Section: Generation Of In Vivo Loss Of Function Cohesin Animal Modelssupporting
confidence: 78%
“…7 C). A similar phenotype has been described previously in an Flt3-ITD animal model (Chu et al, 2012).…”
Section: Generation Of In Vivo Loss Of Function Cohesin Animal Modelssupporting
confidence: 78%
“…Another report has shown that introduction of an IDH2 mutant into FLT3-ITD knockin hematopoietic progenitor cells induced AML (19). Because FLT3-ITD knockin mice develop chronic myelomonocytic leukemia (42,43), mutations have accumulated in FLT3-ITD knockin mice that effectively predispose them to develop AML by introducing the IDH2 mutations. Another report has shown that a xenograft model of IDH2-mutant cells was predisposed to develop sarcomas (20).…”
Section: Discussionmentioning
confidence: 99%
“…We chose mouse models incorporating two common class I mutations observed in human AML: FLT3-ITD (Nakao et al 1996) and Nras G12D (Schubbert et al 2007). Flt3-ITD knock-in mice develop a chronic myelomonocytic leukemia that never progresses to AML (Lee et al 2007;Chu et al 2012), whereas Mx-1-mediated activation of a latent ''lox-stop-lox'' Nras G12D allele (Haigis et al 2008) in hematopoietic cells results in a myeloproliferative disorder Wang et al 2011). …”
Section: Idh2 Mutants Cooperate With Flt3-itd or Nrasg12d To Promote mentioning
confidence: 99%